FIDIC (kırmızı kitap-1999) çerçevesinde uluslararası inşaat sözleşmelerinde yüklenicinin işi zamanında tamamlaması ve iş sahibinin kabulüne hazır hale getirme yükümlülüğü - Wathıe, Dıogoye (My University, 2018)
Çalışmamız üç ana bölümden oluşmaktadır. Birincisi genel olarak FIDIC kapsamında uluslararası inşaat sözleşmelerinden bahsedeceğiz. Bu bölümde üç ana başlık yer almaktadır: Birincisi FIDIC’nın tarihçesi ve yapısı, FIDIC kurallarının hukukî niteliği ve son olarak FIDIC sözleşmeleri üzerinde durulacaktır. FIDIC kırmızı kitap hükümlerinde sözleşmelerin kurulmasına ilişkin açık hükümler zikredilmemiştir.Yüklenicinin işi zamanında tamamlaması yükümlülüğü ve iş sahibinin hakları başlığını taşıyan ikinci bölümde ise, yüklenicinin işe zamanında başlaması ve bitirmesi yükümlülüğü incelenmiştir. Daha sonra yüklenicinin süre uzatım hakkı ve bunun şartları incelenmiştir. Bu bölümde süre uzatımının hangi hâllerde mümkün olacağı değerlendirilmiştir. İş sahibinin işin zamanında tamamlanmaması nedeniyle tazminat hakkı yine bu bölümde ele alınmıştır. Fakat FIDIC kırmızı kitapta gecikme tazminatının niteliği hususunda düzenleme bulunmamaktadır. Ayrıca yüklenicinin işe zamanında başlamaması veya tamamlamaması nedeniyle iş sahibinin sözleşmeyi sona erdirme hakkı da bu bölümde açıklanacaktır. Son olarak iş sahibinin diğer hakları üzerinde durulmuştur.Üçüncü bölümde ise, yüklenicinin işi geçici kabule hazır hale getirmesi ve bu aşamadan sonraki yükümlülüğü değerlendirilecektir. Burada yüklenicinin işi geçici kabulü hazır hâle getirmesi yükümlülüğü ve hukukî sonuçları açıklanmıştır. Bu kapsamda geçici kabul kavramı üzerinde durulmuştur. Bundan sonra ise geçici kabul öncesi ve sonrası yüklenicinin yükümlülükleri ve hukukî sonuçları açıklanmıştır. İş sahibinin ayıptan kaynaklanan haklarını kullanmak için bazı şartları yerine getirmesi gerekir. Bunlardan en önemlisi yükleniciye ayıpları gidermek için makul bir süre vermesidir. Fakat FIDIC kurallarında makul bir sürenin ne olduğu düzenlenmemiştir. Son ana hat yüklenicinin işi kesin kabule hazır hâle getirmesi ve hukukî sonuçlarıdır. Burada kesin kabul kavramı, kesin kabul ilgili işlemleri ve kesin kabulün hukukî sonuçlarından bahsedilmiştir.

The subject of our theses is the contractor’s liability in international construction contracts within the framework of FIDIC -1999 RED book to finish timely the work and make the employer read for acceptance. FIDIC means International Federation Consulting of Engineer and is a professional organization. Our work consists of three main parts. In the first part, we will generally deal about international construction contracts under FIDIC. There are three main headings in this section: The first will focus on the history and structure of FIDIC, the legal nature of FIDIC rules. On this point, it should be noted that although FIDIC is an international federation of professional nature, but it does not have supranational status, so its rules are not mandatory. The last subtitle deals with FIDIC contracts. FIDIC has 7 books called contracts. These are the red book, yellow book, the silver book, the green book, the green book, the gold book, the white book, the blue green paper, the navy blue book. Finally we will deal with the formation of FIDIC contracts. On this point there is no clear provision which deals with the time of the conclusion of the contract.The contractor's obligation to complete the work on time and the employer's rights are discussed in this second tittle. The first heading of this tittle we analyzed the contractor's obligation to start and finish the work on time. Then the contractor's right to extend the time and its requirements has been examined. In this section, it is evaluated in which cases the extension of time is possible. These situations are number 17 listed in Article 8.4 of the FIDIC Red Book (1999). The right to compensation for damage of the employer if the contractor didn’t to complete the work on time is also addressed in this section. But the nature of the damage resulting from the delay is not defined by the Book. Is it a penalty clause or lump sum damage is the question which the doctrine tries to answer? Disputes resulting to the determination of such damage the book put in place some ways of solution. There are DAB, amicable settlement and finally the International Chamber of Commerce .Also the right of the employer to terminate the contract if the contractor didn’t start or not complete the work on time will be explained in this section. Finally, the other rights of the employer are emphasized. In the third part, the contractor will make the work ready for taking over, and the obligation after this step will be evaluated. In this section, the contractor's obligation to issue the taking over of the work and its legal consequences are explained. In this context, the concept of taking over certificate is emphasized. After that, the obligations and legal consequences of the contractor before and after the taking over certificate are explained. Before the issue of takıng over certificate the obligations of contractor include the tests that their failure confers the employer and engineer some rights. After the taking over certificate the obligations of the contractor and their legal consequences are also part of chapter. These consequences relate to the rights of the employer resulting from defects or shortcomings after the issue of taking over certificate. However, the rights of the employer are subordinated to well-defined conditions. And finally in a reasonable time if the contractor does not repair the defects noted the rights of the employer will be due. The second main title of the third chapter is the contractor's work and the legal consequences that it is ready to accept. Here, the concept of performance certificate, the procedures of performance certificate and the legal consequences of the performance certificate are mentioned.
Keywords: Construction contracts; contract; contractor; Contractors; Contracts; FIDIC; Hukuk ve mevzuat; International law; İnşaat sözleşmeleri; international; kırmızı kitap; Law and legislation; Müteahhitler; red book; sözleşme; Sözleşmeler; uluslararası; Uluslararası hukuk; yüklenici FIDIC